2015
DOI: 10.25159/2520-5293/39
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Malaria Treatment and Patient Adherence to Antimalarial Drugs in Southern Ethiopia

Abstract: In Ethiopia the health system is underdeveloped and much of the rural population has limited access to modern health services. The Ethiopian government introduced the Health Extension Program which is a community-based health care delivery system aimed at accessing essential health services such as malaria treatment through its health extension workers (HEWs). The objective of this study was to evaluate factors influencing malaria treatment practice of health extension workers (HEWs) and patient adherence to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This finding is in line with Argaw’s [33] finding that the national survey revealed that health workers adhered to standard recommendations with respect to less than half of malaria patients they encountered. This could partly be due to insistence and pressure from patients to get anti-malaria drugs for febrile illnesses, providers’ clinical beliefs and capacity constraints of health providers to look for other causes of fever, limited patient diagnosis services and practices to identify other aetiologies such as viruses at medium clinics [28, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with Argaw’s [33] finding that the national survey revealed that health workers adhered to standard recommendations with respect to less than half of malaria patients they encountered. This could partly be due to insistence and pressure from patients to get anti-malaria drugs for febrile illnesses, providers’ clinical beliefs and capacity constraints of health providers to look for other causes of fever, limited patient diagnosis services and practices to identify other aetiologies such as viruses at medium clinics [28, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the efficacy of training as a method to improve guideline adherence have yielded conflicting results. Some studies show improvement [ 22 ], while others show minimum or no improvement of healthcare worker practice [ 23 , 24 ]. In this context, wider dissemination of guidelines and extensive training of healthcare workers would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling has shown that the infectivity of an untreated patient is 29–51 times higher than that of a correctly treated patient [ 7 ]. However, adherence to the treatment of illness in general and to antimalarial treatment in particular is not always perfect [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ]. Therapeutic adherence depends on several factors, which are not always easy to identify [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This will help to assess the real impact of antimalarial interventions related to case management and to propose more appropriate improvement measures. Studies conducted in Ethiopia [ 10 ] identified patient-related factors (fear of adverse effects and forgetfulness) and community-related factors such as the perception of drug efficacy. A study conducted in Ghana [ 8 ] identified other factors, including knowledge of the drug and its beneficial effects.…”
Section: Introductionmentioning
confidence: 99%